Area and volume change of glaciers in the Salzburg region, Austria: a new inventory (2008-2018) - Bertolotti, Giulia; Wiesenegger, Hans; Seiser, Bernd; Fischer, Andrea (PANGAEA, 2025)
For this update of the glacier inventory of the Salzburg region (Austria), 172 glaciers across 7 mountain groups in the state of Salzburg were mapped. Two datasets are presented here: one derived from orthophotos and one from hillshaded digital elevation models (DEMs). The most recent glacier boundaries were primarily derived from orthophotos taken in 2018. Exceptions include glaciers No. 5016 and 5017, for which mapping is based on data from 2013, and several glaciers in the Zillertal Alps (Nos. 5148, 5150, 5152, 5153, 5154, 9002, 9003, 9004, 9005), which were mapped using data from 2016 (see Fig. 4, and table "GI5_Salzburg_Gletscherliste_Orthofotos" in Bertolotti and Fischer, 2020 and 2021, attached). These boundaries were used to calculate area changes. For volume change calculations, glacier boundaries correspond to the most recent available LiDAR flight years: 2008, 2009, 2012, 2013, or 2018, depending on the glacier (see Figs. 1–3 and table "GI5_Salzburg_Gletscherliste_DGM" in Bertolotti and Fischer, 2020 and 2021). The updated glacier outlines were mapped based on the 2009 inventory (GI3, Fischer et al., 2015), digital elevation models from the latest survey years (Figs. 1–3), and orthophotos from 2018 (or 2013/2016 in the exceptions noted above). Volume changes were calculated using elevation models from 1998 (GI2). Area changes were also compared with earlier inventories: GI1 (Groß, 1987) and GI2 (Lambrecht and Kuhn, 2007). Almost all glaciers are located along the main Alpine ridge and are distributed across seven mountain groups: Ankogel-Hochalmspitz Group, Glockner Group, Granatspitz Group, Hochkönig Group (also known as the Salzburg Limestone Alps), Sonnblick Group (also known as the Goldberg Group), Venediger Group, and Zillertal Alps. Only the three glaciers in the Hochkönig Group are located outside the main Alpine ridge.
Keywords: Glacier area; Glacier area changes; Glacier inventory; Glaciers; Glaciers_austria; Glaciers Austria; Glacier volume; Glacier volume changes